Wetland Flora of Jagadishpur Reservoir, Western Nepal - Budhathoki, Prativa; Thakur, Chandra Kala; Sandilya, Madan Mohan; Poudel, Basu Dev (Journal of Environment Sciences, 2022)
The Wetland flora of Jagdishpur Reservoir has been studied in the year 2021. This study was conducted to document the wetland flora found on foot trails around the Jagdishpur reservoir, Kapilvastu District. 70 species belonging to 67 genera of 37 families were recorded from the study area.13 species were invasive which seems that the wetland is under threat. Thus; this study provides baseline information about the wetland flora of the reservoir which might help in further research and in the conservation of wetland flora.